Comprehensive multi-modality treatment of thoracic aorta pseudoaneurysms: a single-center experience - Recicarova, Sandra; Jonak, Michael; Netuka, Ivan (General thoracic and cardiovascular surgery, 2024)
INTRODUCTION: Thoracic aorta false aneurysms (TAFA) are unexplored complications after cardiac surgery associated with significant morbidity and mortality. Therefore, the purpose of this study was to examine the clinical profiles, surgical techniques, and operative outcomes, of patients treated for TAFA at a single institution. METHODS: From 1996 to 2022, 112 patients were treated for aortic pseudoaneurysm (mean age 55 ± 14 years, 78 patients were male). In the majority of the patients (90%) TAFA developed after previous cardiovascular surgery, the most common diagnosis and surgical procedure preceding the TAFA development was an aortic dissection (52%) and Bentall procedure (47%). In the rest of the cohort, the leading cause was trauma. RESULTS: Sixty-one percent of patients were indicated for reintervention (surgical reoperation, endoluminal graft implantation, septal occluder implantation, coil embolization, or a combination of procedures). Overall, 52 patients had undergone cardiac reoperation. TAFA was resected and the aorta was repaired in 55% or replaced in 45%. Operative mortality was 5.7%. In postoperative follow-up, a hypoechogenic lesion encircling aortic prosthesis was present in 94%, therefore it was determined as a negative prognostic factor. The mean follow-up was 13.2 ± 19.4 years. CONCLUSION: Although there is no specific approach how to prevent TAFA development, maintaining normal blood pressure and regular follow-up should be applied. More frequent follow-ups should be performed in patients with a hypoechogenic lesion encircling and aortic prosthesis. Early detection during long-term postoperative follow-up, an individually tailored approach of a multidisciplinary team is necessary for favorable treatment outcomes.
Keywords: dospělí; Endovascular Procedures; Female; kombinovaná terapie; Aorta, Thoracic; endovaskulární výkony; Adult; cévy - implantace protéz; výsledek terapie; ženské pohlaví; aneurysma hrudní aorty; Time Factors; časové faktory; lidé; pooperační komplikace; Treatment Outcome; Reoperation; Aortic Aneurysm, Thoracic; Risk Factors; reoperace; retrospektivní studie; Aneurysm, False; Male; Postoperative Complications; Combined Modality Therapy; Aged; aorta thoracica; rizikové faktory; lidé středního věku; nepravé aneurysma; mužské pohlaví; senioři; Blood Vessel Prosthesis Implantation; Retrospective Studies; Middle Aged; Humans